An assessment of red list data for the Pezizomycotina (Ascomycota): Umbria (Italy) as a test case. (2nd November 2018) - Wagensommer, Robert P.; Bistocchi, Giancarlo; Arcangeli, Andrea; Rubini, Andrea; Perini, Claudia; Venanzoni, Roberto; Angelini, Paola
Abstract: A Red List of all 108 Pezizomycotina (Ascomycota) species recorded in Umbria Region (central Italy) is provided. According to the IUCN categories and criteria, 60.18% of the assessed species are classified as threatened, whereas 12.96% are Near Threatened (NT), 1.86% are Least Concerned (LC) and a noteworthy amount of 25% are Data Deficient (DD). As a consequence of the downlisting applied to the majority of the assessed taxa, according to the guidelines for application of IUCN red list criteria at Regional level, only 1.54% of the threatened species is Critically Endangered (CR), while 46.15% are Endangered (EN) and 52.31% are Vulnerable (VU). Given that the present work represents the first complete regional red list of Pezizomycotina in Italy, and that a national, as well as a European red list do not exist to date, it could be considered as a case study for other Italian Regions as well as for other European countries, aiming at the compilation of a national and European red list of this fungal group mostly overlooked in conservation strategies.